Pulpal uptake of mercury from lined amalgam restorations in guinea pigs - (:unkn) unknown (WILEY, 2002)
The aim of the present study was to examine pulp in amalgam-restored teeth of guinea pigs with respect to the presence of mercury, and to evaluate whether lining of cavities with resin modified glass ionomer cements had any effect on the penetration of mercury. Class V cavities were prepared in 63 incisor teeth of 21 guinea pigs. Three amalgam restorations were placed per animal, one without base liner and two with different resin-modified glass ionomer cements (GC Lining LC and Ionoseal). Following observation periods of 1, 7 or 30, teeth were extracted and the mercury concentration in the pulp tissue was evaluated using atomic absorption spectrophotometry. It was found that resin-modified glass ionomer cements significantly diminished the transport of mercury into the pulp between day 7 and day 30 after amalgam insertion.
Keywords: amalgam; glass ionomer cement; guinea pig; mercury; pulp; MECHANICAL-PROPERTIES; CALCIUM HYDROXIDE; LINING MATERIALS; RESIN COMPOSITE; DENTAL AMALGAM; GLASS; PERMEABILITY; ABSORPTION; RELEASE; BLOOD